LILRB1 and LILRB2 genomics and transcriptomics in macaque and baboon species: polymorphism, diversification, and extensive alternative splicing - de Groot, Natasja G.; de Groot, Nanine; Heijmans, Corrine M. C.; de Vos-Rouweler, Annemiek J. M.; van der Wiel, Marit K. H.; Bruijnesteijn, Jesse (Frontiers in Immunology, 2026)
IntroductionInhibitory receptors play a pivotal role in fine-tuning immune responses. The leukocyte receptor complex (LRC) encodes multiple receptor families, including the leukocyte immunoglobulin-like receptor (LILR) family, which next to activating receptors involves several inhibitory receptors. The LILRB1 and LILRB2 receptors are considered immune checkpoint inhibitors, which may interact with MHC class I molecules, and are expressed mainly on monocytes, B- and T-cells.MethodIn this study, we characterized LILRB1 and LILRB2 at the genomic and transcriptomic level in three Old World monkey species, namely rhesus and long-tailed macaques and Hamadryas baboon, using SMRT sequencing on PacBio platforms.Result and discussionWe describe 71 LILRB1 and 58 LILRB2 alleles in the two macaque species, of which only one allele was previously published. In contrast, less polymorphism is observed in the Hamadryas baboon, with only six LILRB1 and seven LILRB2 alleles characterized. Phylogenetic analysis, including known human data, revealed extensive diversification of the LILRB1 and LILRB2 in macaques, with allelic variation clustering into nine and twelve distinct lineages, respectively. This contrasts with the more conserved repertoires observed in humans and Hamadryas baboons. Compared with our experience analyzing MHC and KIR transcriptome data, the LILRB1 and LILRB2 transcriptomes were dominated by alternatively spliced isoforms. Alternative 3’ splice sites near exons 10 and 15 and/or skipping of exon 15, were encountered for most LILRB1 alleles. In LILRB2, the deletion of exon 9 is the most prominent event, next to deletion of exon 10 and the use of alternative 3’ splice sites near exons 10 and 15. The exons that encode the extracellular domains remain largely intact, suggesting that alternative splicing predominantly affects the stem region and the signaling capacity of the LILRB1 and LILRB2 receptors.